Transcriptome responses of Lactobacillus acetotolerans F28 to a short and long term ethanol stress - Xiaopan Yang (Nature Portfolio, 2017)
Abstract Lactobacillus acetotolerans is a major microbe contributing to the Chinese liquor fermentation with unknown function. It can be grown well in a high concentration of ethanol. RNA sequencing (RNA-seq) was performed on L. acetotolerans F28 growing in 12% ethanol to determine important genetic mechanisms for both a short and long term adaption to this environment. A genome-wide transcriptional analysis revealed that the most important genetic elements for L. acetotolerans F28 grown in ethanol are related to high levels of stress response and fatty acid biosynthesis, and a reduction of amino acid transport and metabolism after both a short and long time stress. The fatty acid methyl ester analyses showed that most fatty acids were increased in L. acetotolerans F28 after exposure to ethanol while the unsaturated fatty acid octadecenoic acid (C18:1) was significantly increased. The increasing unsaturated fatty acid biosynthesis in L. acetotolerans F28 might enhance cell membrane fluidity and protect the cells against high concentration of ethanol. Overall, the transcriptome and functional analysis indicated that the elevated stress response and fatty acid biosynthesis, and the decrease of amino acid transport and metabolism might play important roles for L. acetotolerans F28 to adapt to environmental ethanol.